Pengaruh Latihan Teknik Passing Bawah Menggunakan Latihan Dengan Tongkat Pada Siswa Ekstra Bola Voli Putri Smk Pelita Nusantara 1 Semarang (Universitas Negeri Semarang, 2022)
The purpose of this study was to analyze reception movement skills in female athletes of SMK Pelita Nusantara 1 Semarang which were analyzed from the Reception technique using stick media so that they could improve reception movements to be more effective and efficient. Types of research using experiments. The sample was 18 female athletes of SMK Pelita Nusantara 1 Semarang who had the same reception skills, namely not yet mastering reception. The instrument used in this study was a reception test from Richard H. Cox. The results showed that (1) There was a significant effect of lower passing practice using a stick on the accuracy of lower passing for beginners, with a significance value of p 0.000 < 0.05. (2) There is a significant influence of the practice of bottom passing of the stick on the accuracy of the lower passing for beginners, with a significance value of p 0.000 < 0.05. (3) The practice of bottom passing without a stick is not significantly better than the practice of bottom passing with a stick against the accuracy of lower passing for beginners, although there is an average posttest difference of 2.33, greater, but not significantly different (sig p 0.129 > 0.05). The timing of passing the ball, the position of the hands, and the position of the body greatly affect the results of the lower power passing. With the development of the media, it can be a reference for athletes and coaches.